Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How to solve this DE? $$ {dx \over x} = {dy \over y} = {dz \over z - a \sqrt{x^2+y^2+z^2}}$$ From the first part, I get $y = c_1x$. How to find the other solution? The answer according to answer sheet is $ z + \sqrt{x^2 + y^2 + z^2} = c_2$. Thank you for help.

share|improve this question
    
Try putting $w^{2} = x^{2} + y^{2} + z^{2}$ and then use the identity \begin{equation} \frac{a}{b}=\frac{c}{d}=\frac{e}{f}=\frac{k_{1} a + k_{2} c + k_{3} e}{ k_{1} b+ k_{2} d+ k_{3} f}. \end{equation} –  Jayesh Badwaik Aug 2 '12 at 11:39
    
@BabakSorouh the topic is "Simulatneous Equation of first order first degree" –  Santosh Linkha Aug 2 '12 at 11:41
    
@JayeshBadwaik wouldn't i get more variables from substitution? –  Santosh Linkha Aug 2 '12 at 11:44
    
No, basically you then eliminate $x$ and $y$ and solve for $w$ in terms of $z$. If you want more hint, I can give you so. –  Jayesh Badwaik Aug 2 '12 at 11:46
    
okay thanks ... let me try first. –  Santosh Linkha Aug 2 '12 at 11:48

2 Answers 2

up vote 3 down vote accepted

$$ {dx \over x} = {dy \over y} = {dz \over z - a \sqrt{x^2+y^2+z^2}}$$ You get $y=c_1x$, so put it into the third fraction: $$ {dx \over x} = {dz \over z - a \sqrt{x^2+c_1^2x^2+z^2}}$$ $$ {dx \over x} = {dz \over z - a \sqrt{(1+c_1^2)x^2+z^2}}={dz \over z - a \sqrt{Cx^2+z^2}}$$ which is homogeneous equation: $$(z - a \sqrt{Cx^2+z^2})dx=xdz, x\neq 0$$ by taking $u=\frac{z}{x}$, you get: $${-adx \over x} = {du \over \sqrt{C+u^2}}$$ then integrating from both sides gives: $$\ln|u+\sqrt{C+u^2}|=-a\ln|x|+c_2$$ or $$\ln|z+\sqrt{x^2+y^2+z^2}|=(1-a)\ln|x|+c_2$$ Are you sure, you don't have any information about that $a$?

share|improve this answer
    
no ... it isn't given ... must be some arbitrary constant. thank you for your effort –  Santosh Linkha Aug 2 '12 at 12:13

Let

\begin{equation} {\frac{dx}{x}} = {\frac{dy}{y}} = {\frac{dz}{z - a \sqrt{x^2+y^2+z^2}}} = K \end{equation}

\begin{equation} {\frac{2xdx}{2x^{2}}} = {\frac{2ydy}{y^{2}}} = {\frac{2zdz}{2z^{2} - 2az \sqrt{x^2+y^2+z^2}}} = K \end{equation}

Then \begin{equation} \frac{dx^{2}}{2x^{2}} = \frac{dy^{2}}{2y^{2}} = \frac{dz^{2}}{2z^{2} - 2az \sqrt{x^2+y^2+z^2}} = K \end{equation}

Adding all the three terms, we get \begin{equation} \frac{dx^{2} + dy^{2} + dz^{2}}{2x^{2} + 2y^{2} + 2z^{2} - 2az \sqrt{x^2+y^2+z^2}} = K \end{equation}

\begin{equation} \frac{dw^{2}}{2w^{2} - 2az \sqrt{w^{2}}} = {\frac{2zdz}{2z^{2} - 2az \sqrt{x^2+y^2+z^2}}} \end{equation}

Hence, \begin{equation} \frac{dw^{2}}{2w^{2} - 2az \sqrt{w^{2}}} = {\frac{dz}{z - a \sqrt{w^2}}} \end{equation}

And then, \begin{equation} \frac{2w dw}{2w^{2} - 2az w} = {\frac{dz}{z - a w}} \end{equation}

And so, \begin{equation} \frac{dw}{dz}= {\frac{w - az}{z - a w}} \end{equation}

share|improve this answer
    
looks like i really put up a different subs!! –  Santosh Linkha Aug 2 '12 at 12:27
    
Yeah, can happen. ;-) –  Jayesh Badwaik Aug 2 '12 at 12:40
    
thank both of you!! +2 –  Santosh Linkha Aug 2 '12 at 12:50

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.